HYPERTENSION AND AGEING LEAD TO IMPAIRMENT OF MYOGENIC VASOMOTOR MECHANISM, HIPPOCAMPAL EXPRESSION OF GENES INVOLVED IN BETA-AMYLOID GENERATION AND COGNITIVE DYSFUNCTION. (June 2018) - Koller, A.; Toth, P.; Csiszar, A.; Sonntag, W.E.; Ungvari, Z.
Abstract : Objective: Hypertension in the elderly can lead to dysfunctional autoregulation of cerebral blood flow (CBF), leading to increased risk of stroke and the development of Alzheimer's disease (AD), but the underlying mechanisms are still unknown. We hypothesized that hypertension and aging synergistically impair the myogenic constrictor response of cerebral arteries (CA), known to be involved in the autoregulation of CBF and as a consequence, an altered gene expression in the hippocampus will be observable. Design and method: Hypertension was induced in young (3 mo) and aged (24 mo) C57BL/6 mice with chronic (4 wk) infusion of angiotensin II and changes in myogenic response of CA) and hippocampal mRNA expression of genes involved in amyloid precursor protein (APP)-dependent signaling, APP cleavage, A-beta processing and A-beta-degradation, synaptic function were assessed. Results: In MCAs from young hypertensive mice, pressure-induced increases in SMC Ca-signal and myogenic tone were increased, both of which were inhibited by the cytochrome P-450 omega-hydroxylase inhibitor HET0016 and the transient receptor potential (TRP) channel blocker SKF96365. MCAs from aged hypertensive mice did not show adaptive increases in pressure-induced Ca-signal and myogenic tone and responses to HET0016 and SKF96365 were blunted. Aged hypertensive mice exhibited spatial memory impairments in the Y-maze and impaired performance in the novel object recognition assay. Hypertension in aging was associated with changes in hippocampal expression of APP-binding proteins, e.g., [Mint3/amyloid beta A4 precursor protein-binding family. A member 3 (APBA3), Fe65/amyloid beta A4 precursor protein-binding family B member 1 (APBB1)], amyloid beta (A4) precursor-like protein 1 (APLP1), muscarinic M1 receptor, and serum amyloid P component, all of which may have a role in the pathogenesis of late-onset AD. Conclusions: Thus functional maladaptation of aged cerebral arteries to hypertension is due to the dysregulation of pressure-induced 20-HETE and TRP channel-mediated SMC calcium signaling, whereas the hippocampal gene expression signature observed in aged hypertensive mice provides important clues for future studies to elucidate the mechanisms by which hypertension may contribute to the pathogenesis of Alzheimer's disease.